2019
DOI: 10.17979/sportis.2019.5.1.3433
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la relación existente entre el uso de videojuegos y la práctica de actividad física

Abstract: Las Nuevas Tecnologías, y en especial los videojuegos, forman parte de la vida diaria de los niños. El objetivo principal de este estudio es analizar si la práctica de actividad física puede reducir los problemas que genera el uso continuado de los videojuegos. Para ello se analizó una muestra de 220 alumnos y se estudió el uso que hacían de los videojuegos (a través del Cuestionario de Experiencias Relacionadas con los Videojuegos), la actividad física semanal que realizaban y si estaban o no federados (a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…In a study carried out in a sample of 837 children, the time dedicated to video games was negatively related to that for physical activity, that of learning to play an instrument, and that dedicated to artistic activities, to the family, and to free play [3]. Similar results were found in another study [40] carried out with a sample of 220 Primary school students, where it was found that those students who practiced more than 3 h of physical activity per week had fewer problems with video game addiction, so investing in programs enhancing children's adherence to sports in their free time may be an option to prevent problems related to the overuse of electronic devices or video games. In this last study, no gender differences were found in terms of the level of physical activity, as in the present study, where boys and girls show similar values for physical activity during free time.…”
Section: Physical Activity In Free and Leisure Time (Leisure-i)supporting
confidence: 72%
“…In a study carried out in a sample of 837 children, the time dedicated to video games was negatively related to that for physical activity, that of learning to play an instrument, and that dedicated to artistic activities, to the family, and to free play [3]. Similar results were found in another study [40] carried out with a sample of 220 Primary school students, where it was found that those students who practiced more than 3 h of physical activity per week had fewer problems with video game addiction, so investing in programs enhancing children's adherence to sports in their free time may be an option to prevent problems related to the overuse of electronic devices or video games. In this last study, no gender differences were found in terms of the level of physical activity, as in the present study, where boys and girls show similar values for physical activity during free time.…”
Section: Physical Activity In Free and Leisure Time (Leisure-i)supporting
confidence: 72%
“…Sedentary lifestyle associated with new technologies is one of the main factors related to childhood obesity (Chacón Cuberos et al, 2015). New Technologies, and especially video games, are part of children's daily life (Sánchez-Zafra, Ramírez-Granizo, Baez-Mirón, Moreno-Arrebola & Fernández-Revelles, 2019). For these authors (Sánchez-Zafra et al, 2019), the practice of PA reduces the number of students with problems related to video games.…”
Section: Screens and Device Use In Early Childhoodmentioning
confidence: 99%
“…Exergames or active video games are presented as the perfect complement to encourage physical activity focused on the interests of children because of the games' dynamics, their presentation and also because they generate a different motivation and stimulation in each person that is sufficient to improve PA levels [13]. This type of device has become the technological focus of PA, which supplies the needs of users at the moment of exercise, stimulating them through play and physical activity competence [14]. The suppression of peripherals such as the keyboard, controller and mouse, allows the user to move in a real environment and simulate it within the game or virtual reality, where players without the need to be in a passive position (sitting) use movements, body gestures, as well as voice to develop in the different video games.…”
Section: Introductionmentioning
confidence: 99%